Genetic variations among white spot syndrome virus (WSSV) isolates from shrimp farms in Gujarat, north-west coast of India - Patil, Prasanna Kumar; Solanki, Haresh G.; Otta, Subhendu Kumar; Patel, Krishna; Saravanan, P.; Chavali, Gopal; Pillai, Madhusudanan S. (Indian Journal of Fisheries, 2018)
The present paper documents the molecular diagnosis and genotyping of white spot syndrome virus (WSSV) isolates collected from different shrimp farms of Gujarat, north-west coast of India. Preliminary diagnosis was done using single tube PCR and genotyping of isolates by analysis of variable number tandem repeat sequence (VNTRS) in minisatellites viz., ORF 94, ORF 125, ORF 75 and ORF 75 flank. Out of the 79 samples analysed, 32 (33.80%) were positive with low (54.17%), medium (8.33%) and high (37.50%) severity of infection. Genotyping, using ORF 94 revealed that repeat units (RUs) 4 and 11 were the most frequent ones (32%) while ORF 125 showed 5 different repeat types of which RU 5 was the most common (45.83%). Two genotypes were observed for ORF 75, one showed multiple repeats of two 45 bp, followed by a 57 bp, whereas the other showed two repeats that included 5 and 4 repeats of 45 bp. Sequence analysis of the 54 bp variable sequence of ORF 94 RU type 4 revealed single-nucleotide polymorphism (SNP) at 47th base. Based on the results from ORF 94, dominance of RU types 11or 4 were recorded for the first time in India and one sample showed 2 bands of different sizes indicating the prevalence of two different genotypes infecting the same pond at a given time. Further, no correlation could be observed between the virus genotype and the severity of the mortality in the outbreaks. The results suggest the widespread occurrence of WSSV in the region and circulation of distinct virus genotypes.